Law Enforcement Against Bribery Perpetrators and Grantors of Lobster Seed Export Permits at the Ministry of Maritime Affairs and Fisheries - Latief Eko Yuniarto; Raihan Raihan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Corruption becomes an extraordinary act of punishment so that it is necessary to impose the heaviest sentence. The bribery of lobster seeds at the Ministry of Marine Affairs and Fisheries is very sad when viewed from the glasses of the Law. This research uses normative legal analysis by analysing and reviewing both primary and secondary legal materials to obtain legal materials relevant to legal issues that have been formulated in the study. The results of this study are charged with imprisonment for life or imprisonment of at least 4 (four) years and a maximum of 20 (twenty) years, and a fine of at least two hundred million rupiahs and at most one billion rupiahs. The conclusion of this study is the application of criminal enforcement for bribery perpetrators and export licensees according to the provisions of the Corruption Act for state organisers is considered not yet maximal because the minimum illegal conviction period is five years.